Cellular and humoral immunogenicity of the COVID-19 vaccine and COVID-19 disease severity in individuals with immunodeficiency - Murray, C. E.; O’Brien, C.; Alamin, S.; Phelan, S. H.; Argue, R.; Kiersey, R.; Gardiner, M.; Naughton, A.; Keogh, E.; Holmes, P.; Naughton, S.; Scanlon, A.; et al. (Frontiers in Immunology, 2023)
Background A well-coordinated adaptive immune response is crucial for limiting COVID-19 disease. Some individuals with immunodeficiency are at a high risk of developing severe COVID-19. Therefore, the development of standardised methods for measuring different arms of these individuals’ vaccine response is of particular interest. In this study, we compared the vaccine response of individuals living with immunodeficiency with healthy controls in terms of interferon gamma (IFN-γ) production and spike protein-specific antibody level post primary COVID-19 vaccination and booster vaccines. Additionally, the disease severity of those individuals who contracted COVID-19 was assessed. Methods Whole blood was stimulated overnight from 71 participants and 99 healthy controls. Commercially available PepTivator® peptide pool and trimeric spike protein stimulation were used. ELISA was used to analyse IFN-γ levels. The total SARS-CoV-2 spike protein antibody titre was measured using a Roche Elecsys® S total antibody assay. Patient characteristics, COVID-19 infection status and IDDA 2.1 ‘Kaleidoscope’ scores were recorded. Vaccine responses were scored from one to three. Results 99% of healthy controls, 89% of individuals with IEI and 76% with secondary immunodeficiency (SID) had an IFN-γ level above the validated reference range after peptide mix stimulation following the primary vaccination. There was an increase in IFN-γ levels in patients with inborn errors of immunity (IEI) following the booster vaccine (p = 0.0156). 100% of healthy controls, 70% of individuals living with IEI and 64% of individuals living with SID had detectable spike protein-specific antibody levels following the primary vaccination. 57% of those with mild COVID-19 and 11% with moderate/severe COVID-19 had detectable antibody and IFN-γ levels post vaccine. The mean pre-infection IDDA 2.1 scores were higher in individuals who developed moderate/severe COVID-19 (25.2 compared to 9.41). Conclusions Covid whole-blood IGRA is a highly accurate, straightforward and cost-effective assay and can be easily adapted to measure cellular response to COVID-19. A complete evaluation of the vaccine response may be particularly important for individuals living with immunodeficiency. A clinical immunodeficiency score and a validated vaccine response score may be valuable tools in estimating COVID-19 disease risk and identifying individuals living with immunodeficiency who may benefit from enhanced vaccination schedules.